2009
DOI: 10.1021/nl801876h
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water in Super Growth of Single-Walled Carbon Nanotube Carpets

Abstract: The Ostwald ripening behavior of Fe catalyst films deposited on thin alumina supporting layers is demonstrated as a function of thermal annealing in H2 and H2/H2O. The addition of H2O in super growth of single-walled carbon nanotube carpets is observed to inhibit Ostwald ripening due to the ability of oxygen and hydroxyl species to reduce diffusion rates of catalyst atoms. This work shows the impact of typical carpet growth environments on catalyst film evolution and the role Ostwald ripening may play in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
374
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(392 citation statements)
references
References 18 publications
11
374
3
Order By: Relevance
“…8, samples d, e, f͒. 52,53 Indeed, the presence of large amounts of oxygen surrounding Ti atoms prevent particles interaction and thus coalescence of larger cluster.…”
Section: Discussionmentioning
confidence: 99%
“…8, samples d, e, f͒. 52,53 Indeed, the presence of large amounts of oxygen surrounding Ti atoms prevent particles interaction and thus coalescence of larger cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Directly following the deposition of the catalyst layer, an overlayer of alumina (Al 2 O 3 ) 5 nm thick was deposited onto the catalyst. Our recent studies focusing on imaging the morphology of thin catalyst Nano Res (2009) 2: 526 534 films emphasize that catalyst deposition results in the formation of Fe islands due to the balance of the catalyst-surface interfacial interaction relative to the intra-particle atomic interactions [19]. This means that the deposition of the alumina overlayer results in the formation of a continuous film of alumina that not only interacts with the deposited catalyst islands, but also with the carbon surface.…”
Section: Methodsmentioning
confidence: 99%
“…42,44 Experimental studies have also shown that heating using a hot tungsten filament up to 2000°C produces atomic hydrogen that rapidly reduces the catalyst. 16,45 Other strong reducing agents such as ammonia (NH 3 ) 42 and hydrazine (N 2 H 4 ) 46 were also shown to cause the complete reduction of iron oxide. The reduction and phase change of Fe catalyst are therefore dependent on the annealing conditions, such as temperature, pressure, dwell time, and the gas environment.…”
Section: Catalyst Preparation and Treatmentmentioning
confidence: 99%
“…9,16,18,36,[98][99][100] Studying the mechanochemical aspects of CNT growth, wherein the effects of mechanical forces on the catalytic process are analyzed both experimentally and numerically, is an area of current research and will enable better understating and control on the CNT growth process. A deeper understanding of all the competing deactivation mechanisms and identifying the dominant ones will open the door for approaches to overcome them.…”
Section: Outlook On Remaining Challengesmentioning
confidence: 99%
See 1 more Smart Citation